Comparison of smartphone‐based and standard base‐apex electrocardiography in healthy dairy cows. (27th December 2018) - Bonelli, Francesca; Vezzosi, Tommaso; Meylan, Mireille; Nocera, Irene; Ferrulli, Vincenzo; Buralli, Carlotta; Meucci, Valentina; Tognetti, Rosalba
Abstract : Background: There is good diagnostic accuracy of smartphone‐based ECG in the evaluation of heart rate (HR), heart rhythm, and ECG values for humans, horses, dogs, and cats. Objectives: Assess feasibility and reliability of a smartphone ECG device to evaluate HR expressed as beats per minute and ECG values in cows. Animals: Fifty‐five healthy Holstein Friesian cows. Methods: Prospective observational study. A standard base‐apex ECG was acquired for 60 seconds in each cow. A smartphone ECG tracing was recorded simultaneously using a single‐lead bipolar ECG recorder. All ECGs were reviewed by 1 blinded investigator. The following ECG variables were assessed: HR, P wave duration, PR interval, QRS complex and QT interval (milliseconds), P wave, and QRS complex polarity. Agreement between standard and smartphone ECG was evaluated by Cohen's k test and the Bland‐Altman test. Results: Smartphone ECG tracings were interpretable in 89% of the recordings. Minimal differences of no clinical relevance were found between standard and smartphone ECG tracings regarding HR and duration of ECG waves and interval. Good agreement found in the evaluation of QRS complex polarity (85%) but not for P wave polarity ( k = 0.006). Artifacts were rare but of significantly higher frequency in smartphone ECG compared to standard ECG tracings (22% versus 0%; P = .005). Conclusions and Clinical Importance: Good quality single‐lead ECG tracings can be recorded by smartphone device in healthy cows. Smartphone tracings are reliable for evaluation of HR and selective ECG variables. Smartphone ECG can represent an additional tool for ECG screening in cows.